Prevalent Drug Usage Practices in Adults and Children With Idiopathic Inflammatory Myopathies: Registry-Based Analysis From the MyoCite Cohort. Issue 2 (24th March 2022) - Mehta, Pankti; Rathore, Upendra; Naveen, R.; Chatterjee, Rudrarpan; Agarwal, Vikas; Aggarwal, Rohit; Gupta, Latika
Abstract : Background: Idiopathic inflammatory myopathies (IIMs) form a heterogeneous group of disorders with a deficit of quality evidence regarding its management. Therefore, we aimed to explore the prevalent treatment practices in the MyoCite cohort from India. Methods: Drug usage patterns, their predictors, drug retention rates, efficacy, and adverse drug reactions were analyzed for adults and children newly diagnosed with IIM (2017–2020) and followed prospectively and compared with real-world data by performing a medical records review. GraphPad Prism version 8.4.2 was used for statistical analysis. Results: Of 181 adults (male-to-female ratio, 1:4.6) and 30 children (M:F, 1.3:1), dermatomyositis (41% adults, 93% children) was the most common subtype. Methotrexate (MTX) was the drug of choice (67% adult, 90% children) followed by azathioprine (AZA) and mycophenolate mofetil (MMF). The MMF, AZA, cyclophosphamide, and rituximab (RTX) were preferred for those with antisynthetase syndrome (ASSD) and those with lung involvement, whereas MTX was avoided in them. Functional class and family income did not determine drug preferences. Glucocorticoids were initiated at a lower dose in overlap myositis (45% vs 80%, p = 0.001), and the time to achieve the lowest dose of glucocorticoids was longer than 24 months for ASSD (77% vs 14%, p = 0.002). Over a median of 35 months, the overall retention rate was the highest for RTX (75%) followed by MTX (58%). Relapse-free survival was the highest for RTX followed by MTX. The most common reasons for discontinuation were adverse drug reactions for MTX and MMF, inefficacy for AZA, and cost for RTX. Conclusions: In this first analysis of drug usage and retention in patients with IIM in Northern India, MTX emerged as the most preferred drug in both adults and children, with the exception of those with ASSD or lung disease. Organ involvement and subtype of IIM are key determinants of drug preference. Overall, RTX and MTX were well-tolerated with high retention rates, followed by AZA and MMF.